Transpiration in Quercus suber trees under shallow water table conditions: the role of soil and groundwater (Hydrological Processes, 2013)
Water is one of the major environmental factors limiting plant growth and survival in the Mediterranean region. Quercus suber L. woodlands occupy vast areas in the Iberian Peninsula, frequently under shallow water table conditions. The relative magnitude of soil and groundwater uptake to supply transpiration is not easy to evaluate under these circumstances. We recently developed a conceptual framework for the functioning of the root system in Q. suber that simulates well tree transpiration, based on two types of root behaviour: shallow connected and deep connected. Although this significantly improved knowledge on the functional traits of Mediterranean Q. suber, the approach has the limitation of requiring root sap flow data, which are seldom available. In this work, we present alternative methodologies to assess if trees are connected to groundwater and to estimate the soil and groundwater contributions to tree transpiration. We provide evidence on the tree unrestricted access to groundwater solely based on meteorological, stem sap flow and leaf water potential data. Using a soil mass balance approach, we estimated the yearly soil and groundwater contributions to tree transpiration: 69.7% and 30.3%, respectively. Groundwater uptake became dominant in the dry summer: 73.2% of tree transpiration. Results reproduce extremely well those derived from root modelling. Because of its simplicity both in formulation and data requirements, our approach is potentially liable to be adapted to other groundwater- dependent Mediterranean oak sites, where interactions between land use and water resources may be relevant.

Disentangling drought-induced variation in ecosystem and soil respiration using stable carbon isotopes. (Oecologia, 2010)
Combining C flux measurements with information on their isotopic composition can yield a process-based understanding of ecosystem C dynamics. We studied the variations in both respiratory fluxes and their stable C isotopic compositions (delta(13)C) for all major components (trees, understory, roots and soil microorganisms) in a Mediterranean oak savannah during a period with increasing drought. We found large drought-induced and diurnal dynamics in isotopic compositions of soil, root and foliage respiration (delta(13)C(res)). Soil respiration was the largest contributor to ecosystem respiration (R (eco)), exhibiting a depleted isotopic signature and no marked variations with increasing drought, similar to ecosystem respired delta(13)CO(2), providing evidence for a stable C-source and minor influence of recent photosynthate from plants. Short-term and diurnal variations in delta(13)C(res) of foliage and roots (up to 8 and 4 per thousand, respectively) were in agreement with: (1) recent hypotheses on post-photosynthetic fractionation processes, (2) substrate changes with decreasing assimilation rates in combination with increased respiratory demand, and (3) decreased phosphoenolpyruvate carboxylase activity in drying roots, while altered photosynthetic discrimination was not responsible for the observed changes in delta(13)C(res). We applied a flux-based and an isotopic flux-based mass balance, yielding good agreement at the soil scale, while the isotopic mass balance at the ecosystem scale was not conserved. This was mainly caused by uncertainties in Keeling plot intercepts at the ecosystem scale due to small CO(2) gradients and large differences in delta(13)C(res) of the different component fluxes. Overall, stable isotopes provided valuable new insights into the drought-related variations of ecosystem C dynamics, encouraging future studies but also highlighting the need of improved methodology to disentangle short-term dynamics of isotopic composition of R (eco).

Evaporation and carbonic anhydrase activity recorded in oxygen isotope signatures of net CO2 fluxes from a Mediterranean soil (Global Change Biology, 2008)
The oxygen stable isotope composition (δ18O) of CO2 is a valuable tool for studying the gas exchange between terrestrial ecosystems and the atmosphere. In the soil, it records the isotopic signal of water pools subjected to precipitation and evaporation events. The δ18O of the surface soil net CO2 flux is dominated by the physical processes of diffusion of CO2 into and out of the soil and the chemical reactions during CO2–H2O equilibration. Catalytic reactions by the enzyme carbonic anhydrase, reducing CO2 hydration times, have been proposed recently to explain field observations of the δ18O signatures of net soil CO2 fluxes. How important these catalytic reactions are for accurately predicting large-scale biosphere fluxes and partitioning net ecosystem fluxes is currently uncertain because of the lack of field data. In this study, we determined the δ18O signatures of net soil CO2 fluxes from soil chamber measurements in a Mediterranean forest. Over the 3 days of measurements, the observed δ18O signatures of net soil CO2 fluxes became progressively enriched with a well-characterized diurnal cycle. Model simulations indicated that the δ18O signatures recorded the interplay of two effects: (1) progressive enrichment of water in the upper soil by evaporation, and (2) catalytic acceleration of the isotopic exchange between CO2 and soil water, amplifying the contributions of ‘atmospheric invasion’ to net signatures. We conclude that there is a need for better understanding of the role of enzymatic reactions, and hence soil biology, in determining the contributions of soil fluxes to oxygen isotope signals in atmospheric CO2.

Estimation of tree canopy cover in evergreen oak woodlands using remote sensing (Forest Ecology and Management, 2006)
The montado/dehesa landscapes of the Iberian Peninsula are savannah-type open woodlands dominated by evergreen oak species (Quercus suber L. and Q. ilex ssp. rotundifolia). Scattered trees stand over an undergrowth of shrubs or herbaceous plants. To partition leaf area index between trees and the herbaceous/shrubby understorey requires good estimates of tree canopy cover and is of key importance to understand the ecology and the changes in land cover. The two vegetation components differ in phenology as well as in radiation and rainfall interception, water and CO2 ﬂuxes. The main goal of this study was to estimate tree canopy cover in a montado/dehesa region of southern Portugal (Alentejo) using remote sensed data. For this purpose we developed empirical models combining measurements obtained through the analysis of aerial photos and reﬂectance from Landsat Thematic Mapper (TM) individual channels, vegetation indices, and the components of the Kauth–Thomas (K–T) transformation. A set of 142 plots was designed, both in the aerial photos and in the satellite data. Several simple and multiple linear regression models were adjusted and validated. A subset of 75% of the data (n = 106) was used for model ﬁtting, and the remainder (n = 36) was used for model assessment. The best linear equation includes Landsat TM channels 3, 4, 5 and 7 (r 2 = 0.74), but the Normalised Difference Vegetation Index (NDVI), the components of the K–T transformation, and the Atmospherically Resistant Vegetation Index (ARVI) also performed well (r 2 = 0.72, 0.70, and 0.69, respectively). The statistics of prediction residuals and tests of model validation indicates that these were also the models with better predictive capability. These results show that detection of low/medium tree canopy cover in this type of land cover (i.e. evergreen oak woodlands) can be accomplished with the help of high and medium spatial resolution satellite imagery.

Comportement physiologique des glands de chêne liège (Quercus suber L.) durant leur conservation et variabilité inter-individus producteurs (Ann. For. Sci., 2001)
The mature acorns were harvested on twelve selected trees from a cork oak population in Southern Portugal (Herdade da Palma). After drying, the seed lots were stored on three types bags (polyethylene with 30 mm and 50 mm thick and plastic mesh), for six months at 0 oC. At the time of natural dissemination, the acorns from the majority of the trees from the same population were under the same state of morphological and physiological maturity. The moisture content was about 44-47% and a germination rate above 92% . At this time, the germination was very slow because of the existent embryonic dormancy that seems to be dependent on the individual trees. During the storage, germination rate is improved. This might be explained by the breaking dormancy during storage. The mean germination time was on an average 10 days for fresh seeds and decreased to about 4 days after 6 months storage. A relationship between viability and seed moisture content was observed. The Mean Germination Time of dried seed and stored seed for 4 months in plastic mesh bag increased to about 13 days. The germination capacity was strongly decreased when the seed moisture content was below 30%

Effects of acorn storage duration and parental tree on emergence and physiological status of Cork oak (Quercus suber L.) seedlings (Ann. For. Sci., 2001)
This study was conducted to evaluate how parental trees and seed storage duration influenced subsequent seedling physiological status and growth. Seedling emergence rate was higher than 90% independently of the duration of seed storage or parental trees. Seed storage shortened significantly the time and increased the uniformity of seedling emergence. Consequently, the delayed seedling emergence from fresh seeds could be explained by epicotyl dormancy. Seed size varied with parental tree. Seedling growth rate was greatly affected by seed size, independently of storage treatment. Seedlings originating from large seeds (> 5 g) had the fastest growth rates and seedlings from the smallest seeds (< 4 g) had the slowest. Final shoot height, however, depended on the duration of seed storage. The seed size and the duration of storage had a great effect on the initial rate of leaf production, but did not affect the final number of leaves. Leaf chlorophyll concentration was reduced as the duration of seed storage increased but was independent of parental tree (i.e., seed size). Seedling biomass was positively related to seed size. The duration of seed storage reduced the shoot/root ratio, but no significant effect was observed among parental trees. The shoot/root value of seedlings from stored seed was about 1.5 and the one of seedlings from fresh seed was about 2.